PENGARUH PENDIDIKAN KESEHATAN METODE DEMONSTRASI TERHADAP PENGETAHUAN KELUARGA TENTANG GIZI LANSIA DI RW 03 DESA PARAKAN CIOMAS - Royani; Ismi Nurul Hidayati (STIKes IMC Bintaro, 2019)
Introduction: The person who said elderly person who entered the age of 60 years and above. Along with the increasing age so will more often experience impaired health, at this time the absorption of food tend to be reduced so that when up malnourished. Because it needed a good nutrient intake, then the importance of the assistance of family members who have knowledge of nutritional needs required laansia. The knowledge obtained through sensing good vision, hearing and obtained through formal education as well as the natural process of learning or experience. Objective: to know the influence of health education methods of Demonstration Against Family Knowledge about nutrition in the Elderly RW 03 Parakan Ciomas Village. Method: Type of this research is Quantitative Research with Quasi Experimental Design One Group Pretest-Post Test. Population: entire families living with elderly in RW 03 amounted to 81 families. Sample: Sampling technique using Total Sampling. Data analysis using the method of test for Paired Samples T Test. Results: The results of the analysis before and after a test of Paired Samples T Test showed a p value 0.000 knowledge with the default p value < 0.05. Conclusion: there is an influence of knowledge before and after health education